Meningkatkan Hasil Belajar IPA tentang Gaya pada Gerak Benda melalui Metode Ekperimen pada Siswa Kelas IV SDN Cilandak Barat 01 Pagi - Monalisa Monalisa; Muhamad Sofian Hadi; Iswan Iswan (Syntax Corporation Indonesia, 2025)
This study aims to obtain an empirical description of the improvement of student learning outcomes in learning science subject matter to motion of objects through the experimental method in class IV SDN Cilandak Barat 01 Pagi in the 2019/2020 academic year. This study applies Classroom Action Research (Action Research) to the implementation of learning science subject matter to motion of objects through the experimental method in class IV semester 2 students of the 2019/2020 school year SDN Cilandak Barat 01 Pagi. This research was conducted in two cycles, each one meeting cycle. Before the improvement of learning was implemented pre-cycle and the result was 27 students who had not completed it, 87.10%, 4 students were 12.90%. After the improvement was carried out, the results in the first cycle of students who had not completed were 18 students, 58.07% of the children who had completed learning were 13 students at 41.93%, while in the second cycle there were no students who had not completed it by 0% and who had finished learning reached 31 students or 100%. The important finding in this study is that learning science material force on motion of objects through the experimental method in grade IV students can: Increase student activity in learning, increase cooperation to solve a problem, and increase student responsibility for assignments given by the teacher so as to improve the learning achievement of science subject motion through the experimental method in grade IV students.